THE DEVELOPMENT OF THE IDENTIFICATION KEY CIRCLE MEDIA FOR THE SKILLS OF CLASSIFYING ANIMALS AND STUDENTS’ UNDERSTANDING OF CONCEPTS - Yayan Yayan (Indonesian Journal of Learning and Instruction)
This research is motivated by the low skill of classifying animals and the low understanding of students' concepts. Preliminary data show that out of 10 groups only 2 groups are skilled in classifying animals. Therefore, this research was conducted to improve the skills of classifying animals and understanding concepts by using the identification key circle media. The research subjects were 36 students of class VII A of SMPN 4 Kuningan. The research data was obtained from the observation of the students' skills in classifying animals and the concept understanding test. Based on the results of the study, it was found that the skill in classifying animals had increased through the Wilcoxon test, the statistical value of the asymp value was obtained. Sig of 0.01. The working hypothesis will be accepted if the value of asymp.sig , and the value of = 0.05, because the value of asymp.sig = 0.01 0.05 then Ha is accepted, and an increase in students' understanding of concepts from the final data analysis shows that obtained based on the Independent sample test output table in the equal variances assumed section, the Sig value is known. (2-tailed) of 0.00 0.005, so as for decision making in the independent sample t-test, it can be concluded that Ho is rejected and Ha is accepted. Thus, it can be concluded that the identification key circle media can improve students' skills in classifying animals and understanding draft. Keywords: Key circle media identification; animal classification skills; student concept understanding.